2008
DOI: 10.1063/1.3013838
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of contacts to thin film N-polar n-type GaN

Abstract: The electrical characteristics of metallization contacts to a thin film N-polar n-type GaN layer fabricated by a laser lift-off process combined with a dry etching are investigated. It is shown that for Pt Schottky contacts, the Schottky barrier height of the N-polar GaN is 1.27eV, which is larger than that (1.23eV) of reference Ga-polar GaN. Ti∕Al Ohmic contacts to the N-polar GaN experience thermal degradation even at 400°C. Such annealing-induced degradation is explained in terms of the presence of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 15 publications
2
47
1
2
Order By: Relevance
“…Ti/Al/Ni/Au is deposited as an ohmic contact without annealing. [ 27 ] All the FETs have been treated with O 2 plasma to reduce surface state effects. [ 28 ] Due to the thick dielectric layer (250 nm), the FET has relatively high gate voltage.…”
Section: Field Effect Transistormentioning
confidence: 99%
“…Ti/Al/Ni/Au is deposited as an ohmic contact without annealing. [ 27 ] All the FETs have been treated with O 2 plasma to reduce surface state effects. [ 28 ] Due to the thick dielectric layer (250 nm), the FET has relatively high gate voltage.…”
Section: Field Effect Transistormentioning
confidence: 99%
“…Here, note that the n value, which was calculated using the relation of n=(E00/kT)coth(E00/kT), was much larger than 1.0 for all cases, indicating that non-ideal carrier transport occurred at the ITO contact interface. According to previous studies, [15,16] carrier transport through surface states associated with point defects such as nitrogen vacancies or oxygen interstitials (generated during ITO sputtering) or threading dislocations might be responsible for the nonideal transport at the contact interface. Notably, however, the n value decreased significantly with post-thermal annealing, indicating that the density of surface states were reduced.…”
Section: Resultsmentioning
confidence: 99%
“…One of the ways of maximizing the EQE is to increase current injection by forming low resistance ohmic contacts and thereby to increase radiative recombination efficiency [9][10][11][12][13]. For c-plane n-GaN, Ti/Al-based metal contacts have been widely investigated because Ti/Al-based schemes easily formed low-resistance ohmic contact when annealed above 600 °C [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1] It is well known that these polar LEDs suffer from the quantum-confined Stark effect (QCSE) [2] induced by large polarization-induced internal electric fields, resulting in a separation between the electron and hole wave functions in the quantum wells (QWs) and so reducing radiative recombination efficiency. [3][4][5] Thus, to enhance the internal quantum efficiency by eliminating or minimizing the Stark effect, GaN-based LEDs were grown on non-polar or semipolar substrates, e.g., (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) plane substrates [5][6][7][8]. For example, Chakraborty et al [6], investigating the DC and pulsed performance of InGaN/GaN multipleQWs LEDs grown on non-polar free-standing m-plane GaN substrates, showed that packaged LEDs (300 × 300 µm 2 ) (a wavelength of 452 nm) yielded a CW output power as high as 0.6 mW at a current of 20 mA, corresponding to an external quantum efficiency of 1.09%.…”
Section: Introductionmentioning
confidence: 99%